The Adrenal Reset Diet : strategically cycle carbs and proteins to lose weight, balance hormones, and move from stressed to thriving - Christianson, Alan (Harmony, 2014)
"The Adrenal Reset Diet is the first scientifically sound, patient-tested weight-loss plan developed by a natural endocrinologist, Dr. Alan Christianson. He heals readers in any of the three stages of adrenal impairment--Stressed, Wired and Tired, or Crashed. Readers learn their stage and receive distinct strategies for diet, activity, and lifestyle change to bring them to Thriving. Recent study participants halved their cortisol levels in just 30 days--and lost an average of 9 pounds!"--